Deverbalization and gramatical structure in simultaneous interpreting - Castro Yáñez, Ginette Gabriela; Chaparro Inzunza, Waldo Boris (Onomázein, 2014)
Different cognitive and psycholinguistic models have been proposed in order to explain and describe the characteristics of simultaneous interpreting. One of those models is the meaningbased processing, in which the deverbalization process is found. It consists in the extraction of the text’s meaning out of its grammatical structure. This transversal, qualitative and exploratory research aims to obtain evidence about this process, through the comparison of the grammatical structures presented by both the source and target texts. To achieve this goal, the structural features from six participants’ output were analyzed. Ten phenomena were detected and their characteristics were described. They present empiric evidence for and against deverbalization.